PENGARUH FREE CASH FLOW, LIKUIDITAS DAN KEPEMILIKAN ASING TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Oktariyani Oktariyani; Afriyanti Hasanah (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2019)
This study aims to determine the effect of free cash flow, liquidity and foreign ownership on debt policies in companies listed on the Indonesia Stock Exchange. The samples used in this study are basic and chemical sector companies listed on the Indonesia Stock Exchange for the 2012-2016 period. The independent variables in this study are free cash flow, liquidity and foreign ownership. The control variable in this study is asset structure. The research method uses a quantitative approach with multiple linear regression analysis techniques. The result of this study is that liquidity affects debt policy because the higher the level of liquidity of the company, the greater the company's ability to pay debts. Foreign ownership affects debt policy because foreign ownership can improve the performance and supervision of managers in the company, especially in determining funding decisions including debt policy, while free cash flow has no effect on debt policy, this is because companies tend to prioritize the use of free cash flow funds for investment and operational needs of the company. This research can be used as a reference for companies in determining funding decisions through debt policy so that the funding decisions taken are more effective.